2011
DOI: 10.1111/j.1438-8677.2011.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen:ovule ratio and its relationship with other floral traits in Papilionoideae (Leguminosae): an evaluation with Argentine species

Abstract: The pollen:ovule ratio (P/O) has traditionally been used as a rough estimator of plant breeding systems. It has been shown that plant breeding systems are associated with particular floral traits. In this study, we determined the P/O in 21 Leguminosae species from Argentina and explored relationships between P/O and taxonomic position, flower size, floral rewards, pollen presentation and pollination mechanisms. According to the results, 15 out of the 21 species classified were obligate xenogamous, although som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 65 publications
0
27
0
3
Order By: Relevance
“…(Ortega-Olivencia & al., 1997) but not in 21 papilionoid legumes (Etcheverry & al., 2012).P/O ratio was not correlated with stigma area in the Passiflora species analysed, perhaps because stigma area was not so different between them. On the contrary, P/O ratio was inversely related to the stigmatic area in two species of Stylidaceae and eight species from three genera of Proteaceae (Cruden, 1997).…”
Section: P/o Flower Size Stigma Area and Sa/pbamentioning
confidence: 99%
See 3 more Smart Citations
“…(Ortega-Olivencia & al., 1997) but not in 21 papilionoid legumes (Etcheverry & al., 2012).P/O ratio was not correlated with stigma area in the Passiflora species analysed, perhaps because stigma area was not so different between them. On the contrary, P/O ratio was inversely related to the stigmatic area in two species of Stylidaceae and eight species from three genera of Proteaceae (Cruden, 1997).…”
Section: P/o Flower Size Stigma Area and Sa/pbamentioning
confidence: 99%
“…Instead, a tendency to xenogamy or autogamy within various taxa at different levels (genus or tribe) of Polemoniaceae (in which P/O ratio is a good predictor of the breeding system) was perceived by Plitmann and Levin (1990). P/O variations were associated to genus but not to tribe in 21 papilionoid Legumes (Etcheverry & al., 2012). Jürgens & al (2002) suggested that taxonomy is indirectly related with P/O as a consequence of the combination of features typical of each taxonomic group.…”
Section: P/o and Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Lopez et al (1999) recorded explosive pollination mechanism with highest pollen-ovule ratios in certain genera of the Fabaceae such as Cytisus, Pterospartum, Teline, Ulex, Stauracanthus and Cytisophyllum. Etcheverry et al (2012) noted that the Fabaceae plants which they studied with explosive pollination mechanism had intermediate pollen-ovule ratios. Padmavathi et al (2012) reported that Indigofera barberi with explosive pollination mechanism had intermediate pollenovule ratio.…”
Section: Discussionmentioning
confidence: 99%